UNIT FOR RESTORATION OF GRAIN BASIS OF HIGH-SILICA SANDS - A. P. Melnikov; Ju. A. Shpuj; B. V. Kurakevich; A. S. Chervjak; Ju. E. Kazuchits (Литьë и металлургия)
The complex of equipment for processing of the waste formed as a result of rejection of cores is considered.